Why evidence-based dentistry? - Gordon D. Douglass (Universidade Estadual de Campinas, 2015)
Evidence-based dentistry will play an important role in dentistry's future efforts to control the ravages of diseases affecting the orofacial complex. The historical record suggests that human dental care derived from early attempts to retain or replace teeth lost to accidents or disease, and this paradigm has served us well for hundreds, if not thousands, of years. More recently, research has enabled man to fight dental disease in ways not previously thought possible. Fluoridation and the increasing significance of genetic intervention, for example, have opened entirely new avenues of dental care, which suggest revolutionary changes in future dental care. For a restorative-based healthcare profession like dentistry, the diagnosis and treatment of patients using these advances will require a significant change in mind-set. This paper will briefly discuss historical events leading to the present state of dentistry, suggest changes that restorative dentists will have to make to survive, and the role evidence-based dentistry must play in an evolving new dental care paradigm.